Digitizing Sacks? Approaching social media as data. (December 2017) - Housley, William; Webb, Helena; Edwards, Adam; Procter, Rob; Jirotka, Marina
During the course of this article, we explore ethnomethodological principles in relation to approaching social media as data. More specifically, we consider the extent to which the work of Harvey Sacks and his rich intellectual legacy might inform this nascent field of empirical inquiry. This exploration is realised in the context of interdisciplinary research at the interface of social and computational science. Drawing from an extensive range of empirical projects into social media we reflect on the efficacy and limitations of these principles (Sacks, 1992) for understanding social media interaction as open data and practical action in the digital age.